Evaluation Of Landfill Management At Gunung Kupang Landfill, Banjarbaru City - Atthaya Namira Yulianto, Khenza; Warmadewanthi, Idaa (Publisher Cv. Inara, 2025)
Banjarbaru City is the capital city of South Kalimantan Province with waste generation in 2023 of 67,854,410 kg/year. Based on the Banjarbaru City Waste Masterplan for 2021-2025 supported by Banjarbaru City Regulation No. 5 of 2023, one strategy to reduce the amount of waste dumped in landfills is the optimization and development of waste infrastructure including landfills. Waste management at the Gunung Kupang Landfill has not been optimal when viewed from the capacity of waste management. One strategy in the policy of 'Increasing Service Coverage and Quality of Management Systems' in the Masterplan is the rehabilitation of landfills that pollute the environment. Before the landfill was decided to be rehabilitated, an evaluation was carried out using the ARRPET (Asian Regional Research Program on Environmental Technology) method. An overall evaluation of the existing conditions at the Gunung Kupang Landfill has never been carried out so it needs to be carried out using the ARRPET method. The results of the environmental evaluation of the existing conditions of the Gunung Kupang Landfill with ARRPET produced a risk index score of 529.24. This value is included in the risk index with a moderate category so that the recommended follow-up is to rehabilitate the landfill into a sustainable landfill as soon as possible. Therefore, it is planned to build a methane gas installation and landfill mining in landfill zone 2 as a rehabilitation method so that the potential for environmental pollution can be minimized and the life of the landfill can be extended. Based on the evaluation results, the rehabilitation method is feasible to be carried out where the NPV of both rehabilitation methods is positive and the BCR is more than 1.